Comparative effects of implanted electrodes with differing contact patterns on peripheral nerve regeneration and functional recovery. (August 2019) - Yu, Ai-Ping; Shen, Yi-Jie; Qiu, Yan-Qun; Li, Jie; Shen, Yun-Dong; Wang, Xiao-Min; Cong, Meng; He, Qian-Ru; Chen, Qing-Zhong; Jiang, Su
Highlights: Point or 1/4 circle contacts promoted sciatic function recovery. Point or 1/4 circle contacts enhanced the regeneration of injured sciatic nerve. Point or 1/4 circle contacts caused less mechanically induced injury. Abstract: Electrical stimulation could enhance nerve regeneration and functional recovery. The objective of this study was to evaluate the regenerative effects of implanted electrodes with different contacts in resected sciatic nerve. Sciatic nerve resection and microsurgical repair models were established and randomly divided into four groups (point contact, 1/4 circle contact; whole-circle contact; no electrodes as control). Electrical stimulation was performed and electrophysiological, morphological and histological exams (of the sciatic nerve and muscle) were conducted at 4 and 10 weeks post-implantation. Point and 1/4 circle contact groups showed significantly higher scores in the sciatic functional index (SFI), increased amplitude of compound muscle action potential (AMP) and motor nerve conduction velocity (MNCV) compared to the control group at both 4 and 10 weeks post-implantation. Point and 1/4 circle contact morphologically promoted sciatic nerve regeneration and reduced muscular atrophy with less mechanical injury to the nerve trunk observed compared with the whole-circle contact group at both 4 and 10 weeks post-implantation. Electrodes with point and 1/4 circle contacts represented an alternatively portable and effective method of electrical stimulation to facilitate injured sciatic nerve regeneration and reduce subsequent muscular atrophy, which might offer a promising approach for treating peripheral nerve injuries.